Assessing the fuel burn and CO2 impacts of the introduction of next generation aircraft: A study of a major European low-cost carrier - Budd, Thomas; Suau-Sanchez, Pere (Elsevier, 2016)
he introduction of more fuel-efficient ‘next generation’ aircraft has the potential to yield benefits for fuel burn and CO2 emissions over current generation aircraft. This has important implications in terms of airline fuel costs and competition, but also for compliance with future environmental legislation and market based incentive schemes. In Europe, major low-cost carriers such Ryanair, easyJet, and Norwegian Air Shuttle have been active in updating their fleet, and they now operate some of the youngest fleets in the industry. Subsequently, the paper assesses the possible fuel burn and CO2 impacts of the introduction of next generation aircraft by employing OAG data and EUROCONTROL's ‘Small Emitters Tool’ to determine the annual fuel burn and CO2 emissions for easyJet, a major European low-cost carrier. Estimations were then made regarding the potential impacts on fuel burn and CO2 emissions from the introduction of the airline's next generation of aircraft under three fleet plan scenarios. Analysis indicates that while new aircraft may allow airlines to increase the capacity in their network with only a marginal increase in overall fuel burn and CO2 emissions, this is unlikely to lead to substantial overall reductions in total fuel burn and emissions, at least in the short term.
Keywords: Aviation; Environment; Low-cost carriers; CO2; Fuel burn